On the identity of Lophostoma silvicolum occidentalis (Davis & Carter, 1978) (Chiroptera: Phyllostomidae) - Velazco, Paúl M.; Cadenillas, Richard (Zootaxa, 2011)
The Neotropical bat genus Lophostoma (Phyllostomidae: Phyllostominae) currently includes seven species. Two taxa, Lophostoma aequatorialis and Lophostoma silvicolum occidentalis, occur west of the Andes in Ecuador and Peru. In the description of L. aequatorialis, these two taxa were compared solely on the basis of morphology because DNA sequence data could not be obtained from the type series of L. s. occidentalis. Here, comparisons are based on molecular data and extensive morphological comparisons. The congruence between the morphological and molecular variation in our analyses support the recognition of L. occidentalis as a valid species and the consideration of L. aequatorialis as a junior synonym of L. occidentalis. Phylogenetic analysis of Lophostoma based on cytochrome-b sequences indicates that L. occidentalis is closely related to L. schulzi. L. occidentalis can be recognized by its white to pale post-auricular patches; dorsal side of the forearm naked; well-developed lateral projection of mastoid process; wide basioccipital; shallow basisphenoid pits weakly separated by a septum; P3 and P4 distal accessory cusp present; M1 ectocingulum strongly developed; M1 mesostyle absent; M1 mesostylar crest present; M1 anterior ectoflexus deep and posterior ectoflexus shallow; M1 lingual cingulum present; M2 mesostyle absent; and M2 mesostylar crest present.